2015
DOI: 10.1016/j.mrfmmm.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule PCR analysis of an unstable microsatellite for detecting mutations in sperm of mice exposed to chemical mutagens

Abstract: Single-molecule PCR (SM-PCR) analysis of long and repetitive DNA sequences, known as expanded simple tandem repeats (ESTRs), has been the most efficient method for studying germline mutation induction in endogenous sequences to date. However, the long length of these sequences makes mutation detection imprecise and laborious, and they have been characterized only in mice. Here, we explore the use of unstable microsatellite sequences that can be typed with high precision by capillary electrophoresis as alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Other studies have associated BaP exposure, not only with the mutagenic and carcinogenic effects on somatic cells (17,19,21), but also with the negative impact on follicular and ovarian development (23,25,26). To determine whether BaP would deteriorate the oocyte quality and weaken the female fertility, we examined oocyte maturation and fertilization processes, two crucial events and key indicators of the high-quality oocyte in female reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have associated BaP exposure, not only with the mutagenic and carcinogenic effects on somatic cells (17,19,21), but also with the negative impact on follicular and ovarian development (23,25,26). To determine whether BaP would deteriorate the oocyte quality and weaken the female fertility, we examined oocyte maturation and fertilization processes, two crucial events and key indicators of the high-quality oocyte in female reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…When BaP is released into the air, it can move into the atmosphere, land, or water (16). In addition to the well-known mutagenic and carcinogenic effects of BaP on the pulmonary cells in both animals and humans (17)(18)(19)(20)(21)(22), accumulating data have indicated that BaP is toxic to the female reproductive system (23)(24)(25)(26)(27). It has been reported that significantly increased levels of BaP are found in the follicular fluid of female smokers, who have more exposure to PAHs than nonsmoking people (28).…”
mentioning
confidence: 99%
“…The extracted DNA was quantified using a Qubit fluorometer (Thermo Fisher Scientific, Waltham, MA) and diluted to 30 pg/μl concentration in 5 mM Tris-HCl (pH 7.5) supplemented with 5 ng/µl carrier herring sperm (Thermo Fisher Scientific). The MSI assay was performed using single-molecule PCR (SM-PCR) [26][27][28]. Three microsatellites, two mononucleotide repeats A27 and A33 [29], and a dinucleotide repeat D14Mit15 [7] were assayed for MSI.…”
Section: Dna Extraction and Single-molecule Msi Analysis By Pcrmentioning
confidence: 99%
“…For expanded simple tandem repeat this involves agarose gel electrophoresis and Southern blotting, whereas for microsatellites sizing is done by capillary electrophoresis. Detailed methodologies for this approach are found in Yauk et al (2002) and Beal et al (2015).…”
Section: Germ Cellsmentioning
confidence: 99%